Evaluation of screening and treatment of cryptococcal antigenaemia among HIV‐infected persons in Soweto, South Africa1. Issue 8 (17th February 2015) - Govender, NP; Roy, M; Mendes, JF; Zulu, TG; Chiller, TM; Karstaedt, AS
<x xml:space="preserve">Abstract</x> Objectives We retrospectively evaluated clinic‐based screening to determine the prevalence of cryptococcal antigenaemia and management and outcome of patients with antigenaemia. Methods Cryptococcal antigen (CrAg) screening of HIV‐infected adults who attended the HIV clinic at Chris Hani Baragwanath Hospital was conducted over 19 months. Data collected from CrAg‐positive patients included CD4 T‐lymphocyte count at screening, prior or subsequent cryptococcal meningitis (CM), antifungal and antiretroviral treatment and outcome after at least 8 months. Results Of 1460 patients with no prior CM, 30 (2.1%) had a positive CrAg test. The prevalence of antigenaemia among patients with a CD4 count < 100 cells/μl and no prior CM was 2.8% (20 of 708). Of 29 evaluable CrAg‐positive patients with no prior CM, 14 (48%) did not return for post‐screening follow‐up. Of these 14, five developed CM and one (7%) was known to be alive at follow‐up. Of 15 patients who returned for follow‐up, two already had evidence of nonmeningeal cryptococcosis. Overall, 11 received fluconazole, one did not and fluconazole treatment was unknown for three. Among these 15, one developed CM and 10 (67%) were known to be alive at follow‐up. Overall, 18 (62%) of 29 CrAg‐positive patients died or were lost to follow‐up. Seven (0.5%) of 1430 CrAg‐negative patients developed CM a median of 83 days post‐screening (range 34 to 219 days). Conclusions Loss to follow‐up is the major operational issue relevant to scale‐up of screen‐and‐treat. Patient outcomes may be improved by rapid access to CrAg results and focus on linkage to and retention in HIV care.